The effect of usability, information quality, and accessibility on the intensity of the madrasa website use at Madrasah Aliyah level - Novianni Anggraini; Purwanto Purwanto; Rochmat Budi Santosa (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
The majority of academic communities in madrasa access the madrasa website infrequently. It is related to the user’s perception of the madrasa website’s quality. This study seeks to determine how usability, information quality, and accessibility effect the frequency with which madrasa websites are visited. This study proposes a correlational quantitative research methodology. The research cohort consisted of 2401 MAN Surakarta students, and the sample size was 96. The method of sampling is proportional random sampling. Data collection techniques using a questionnaire. Techniques of data analysis utilizing correlation analysis and single regression to test the hypotheses of single correlation, correlation, and multiple regression. The results of the study indicate that: 1) Usability has a positive effect on the intensity of website use; 2) Information quality has a positive effect on the intensity of website use; 3) Accessibility has a positive effect on the intensity of website use; and 4) Usability, information quality, and accessibility all have a positive effect on the intensity of website use. Usability, information quality, and accessibility collectively contribute 51.1% to the website's intensity, while the remaining 48.9% is influenced by unmeasured variables.